Molecular and Functional Characteristics of DNA Polymerase Beta-Like Enzymes From Trypanosomatids - Maldonado, Edio; Morales-Pison, Sebastian; Urbina, Fabiola; Solari, Aldo (Frontiers in Cellular and Infection Microbiology, 2021)
Kinetoplast genome integrity is key to T. cruzi cell survival and viability. Kinetoplast DNA is usually under attack by reactive oxygen and nitric species (ROS and RNS) producing damage on the DNA and the cells must remove and repair those oxidatively generated lesions in order to survive and proliferate. Base excision repair (BER) is a well-conserved pathway for DNA repair after base damage, single-base loss and single strand breaks which can arise from ROS, RSN, environmental genotoxic agents and UV irradiation. A powerful BER system has been described in the T. cruzi kinetoplast and it is mainly carried out by DNA pol β and DNA pol β-PAK which are kinetoplast-located in T.cruzi and in other Trypanosomatids. Both DNA pol β and Pol β-PAK belong to the X-family of DNA polymerases and perform BER in Trypanosomes and they have intrinsic 5 -deoxyribose phosphate (dRP) lyase and DNA polymerase activities. However, only DNA Pol β-PAK is able to carry out trans-lesion synthesis (TLS) across 8oxoG lesions. T. cruzi cells overexpressing DNA pol β are more resistant to ROS and are also more efficient to repair 8oxoG compared to control cells. DNA pol β seems to play a role in kinetoplast DNA replication, since it associates with kinetoplast antipodal sites in those development stages in T. cruzi which are competent for replication. ROS treatment of cells induce the overexpression of DNA pol β, indicating that plays a role in kinetoplast DNA repair. In this review we will summarize the main biochemical characteristics of DNA pol β and the involvement in BER and kinetoplast DNA replication. We also summarize key structural features of Trypanosomatid DNA pol β compared their mammalian counterpart.